Technology in the Era of COVID-19: A Systematic Review of Current Evidence - Mehraeen, Esmaeil; Mehrtak, Mohammad; SeyedAlinaghi, SeyedAhmad; Nazeri, Zahra; Afsahi, Amir M.; Behnezhad, Farzane; Vahedi, Farzin; Barzegary, Alireza; Karimi, Amirali; Mehrabi, Nahid; Dadras, Omid; Jahanfar, Shayesteh (Infectious Disorders - Drug Targets, 2022)
Background: During the COVID-19 pandemic, the use of technology-based services has been incremental by the care providers for patients scheduling, regulatory considerations, resource allocation, thus enabling virus exposure prevention while maintaining effective patient care. This study aims to review the currently available evidence to identify available technology solutions in the era of COVID-19. Methods: A systematic review in July 2020 using the PubMed, Scopus, Embase, Science Direct, and Web of Science databases has been carried out. After evaluating the title and abstract to select the most relevant studies based on inclusion and exclusion criteria, the selected articles underwent quality assessment. The full text of selected articles was then thoroughly evaluated to extract the essential findings. Results: In this study, 20 technology-based approaches have been identified for provision of healthcare services to patients with COVID-19. These methods included telemedicine, virtual visits, e-consult, tele-consulting, video conference, virtual healthcare, mobile-based self-care, social media, tele ICU, 3D printing technology, telemonitoring, teleradiology, telesurgical, and cloud-based service. Conclusion: Due to the rapid spread of the coronavirus, the use of technology-based methods for the provision of remote healthcare services can help control the disease. The effectiveness of each of these approaches can be investigated in future research.
Keywords: Technology